The Small-medium Enterprise in New Zealand - Li, Zhang; Wang, Shiyun (Advances in Social Sciences Research Journal, 2015)
The small-medium enterprise (SME) plays a significant role in New Zealand economy, which consists of average 95% small enterprises. The purpose of this paper is to mainly examine which and how e-local government strategy related to SME influence and exploit the expansion of the small business industry through analysing the following three questions; thus taking advantage of the economic growth all over the New Zealand market. This essay will search the components of e-local government strategy related to SMEs from 80 local councils in New Zealand, then determine what has been implemented by these councils via tables, and create an evaluation criterion to show the three most useful components to advance the small business based on the following table.